Compound Containment : A Reigning Power's Military-Economic Countermeasures against a Challenging Power - Kim, Dong Jung (Book collections on Project MUSE., 2022)
When does a reigning great power of the international system supplement military containment of a challenging power by restricting its economic exchanges with that state? Scholars of great power politics have traditionally focused on examining a reigning power's military containment of a challenging power. In direct contrast, Compound Containment demonstrates that these conventional studies are flawed without a sound understanding of the multilayered aspects of containment strategy in great power politics. Since economic capacity and military power are intimately linked to one another, countering a challenging power requires addressing both economic and military dimensions. Nonetheless, this nexus of security and economy in a reigning power's response to a challenging power cannot be explained by traditional theories that dominate research in international security. Author Dong Jung Kim fills a gap in the scholarship on great power competition by investigating when a reigning power will make its military containment of a challenging power "compound" by simultaneously employing restrictive economic measures. Its main theoretical claims are corroborated by an analysis of key historical cases of reigning power-challenging power competition. This book also offers policy prescriptions for the United States by examining whether the United States is in a position to complement military containment of China with restrictive economic measures